SAP BusinessObjects Dashboards 4.1 cookbook : over 100 simple and incredibly effective recipes to help transform your static business data into exciting dashboards filled with dynamic charts and graphics /: over 100 simple and incredibly effective recipes to help transform your static business data into exciting dashboards filled with dynamic charts and graphics. (2015) - Lai, David; Hacking, Xavier
No abstract available